MULTIPLIKASI EMBRIO SOMATIS TANAMAN ANGGREK (Dendrobium sp) DENGAN PEMBERIAN KINETIN DAN SUKROSA SECARA IN-VITRO - PEBRA HERIANSYAH (Jurnal Ilmiah Pertanian, 2019)
The objective of the study was to obtain the combination of sucrose and kinetin concentration reducted in the best effect on Dendrobium explant. This research was conducted in laboratory of tissues culture in Balai Benih Induk Dinas Pertanian and Peternakan Provinsi Riau Pekanbaru from April to June 2015. The experiment was designed using completely randomized design (CRD), factorial consisting of two factors with three replications, the first factor was sucrose with four level respectively 0, 25, 50,75 g L-1 medium. The second factor was kinetin with four level : 0, 0,1, 1,0, 10 mg L-1. The optimum interaction between effect of sucrose and kinetin for percentage of life explants, age bud formation, percentage of explant forming buds, the number of shoot, a percentage of explant producing root was 50 g L-1 sucrose and 1,0 mg L-1 kinetin. Application of sucrose significantly effect age of bud formation, percentage of explant forming buds, number of shoot, shoots high, percentage of explant producing root, number of root, root high, root and shoot ratio (T/R Ratio). Sucrose at 50 g L-1 medium being the best consentration and Kinetin 1,0 mg L-1 being the best consentration.